O modelo em rede aplicado ao segmento de telecomunicações brasileiro - o caso TELEMAR - Fernandes, Maria Fernanda Gomes (2000)
Virtual, cellular, modular, organic, holographic, networked enterprise. This is a new kind of organizational structure of growing importance inside of the enterprises that are looking for new models, attending to the requirements of flexibility, celerity and competitiveness. Requirements to the business of the future, for the new times of moving cycles, each time faster and faster. In that context, technological, cultural, strategic and human aspects are remodelled inside of the context of the called 'Information Era'. The objective of this work is to research how business, specially the Brazilians, are getting ready to be the 'organizations or enterprises' of the future. On the perspective of a virtual organization, throughout the flexibility, celerity and based on knowledge. Especially the Brazilian telecommunication industry, living the post privatization phase, which is in a process of organizational reestructuration, seeking to increase its competition in the globalized market. That is why, the analysis focus on Telemar, one of the largest in terms of geographic covering and investment power in the market and with essentially national shareholders.